2007
DOI: 10.1021/bm070374l
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic Enzymes with Improved Activity and Selectivity upon Adsorption on Polymeric Nanoparticles

Abstract: Nanostructured polystyrene (PS) and polymethylmethacrylate (PMMA) were used as carriers for the preparation of bioconjugates with lipolytic enzymes, such as Candida rugosa lipase (CRL) and Pseudomonas cepacia lipase (PCL). Simple addition of the lipase solution to the polymeric nanoparticles under protein-friendly conditions (pH 7.6) led to the formation of polymer-enzyme bioconjugates. Energy filtered-transmission electron microscopy (EF-TEM) performed on immuno-gold labeled samples revealed that the enzyme p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 40 publications
1
43
1
Order By: Relevance
“…Compared to studies by other researchers, the immobilized lipases were more stable during reuse and storage. [6,8,15,16] Previous reports showed that lipase from Paeudomonas cepacia has the greatest methanol resistance among different lipases; consequently, the Paeudomonas cepacia lipase (lipase L3) has often been used in enzymatic transesterification reactions. [17,18] In this study, the immobilized lipase L3 was investigated for its activity in biodiesel production.…”
mentioning
confidence: 99%
“…Compared to studies by other researchers, the immobilized lipases were more stable during reuse and storage. [6,8,15,16] Previous reports showed that lipase from Paeudomonas cepacia has the greatest methanol resistance among different lipases; consequently, the Paeudomonas cepacia lipase (lipase L3) has often been used in enzymatic transesterification reactions. [17,18] In this study, the immobilized lipase L3 was investigated for its activity in biodiesel production.…”
mentioning
confidence: 99%
“…Enzymes can be attached onto polymeric nanoparticles via physical adsorption, covalent bonding, cross-linking or a combination thereof (Akgol et al, 2009;Daubresse et al, 1994;Matsuno and Ishihara, 2009;Palocci et al, 2007;Watanabe and Ishihara, 2004). Various polymeric materials and immobilization strategies have been designed for attaching enzymes.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Also, many enzymes, e.g., lipases, improve their activity upon the adsorption onto nanostructured carrier materials [106].…”
Section: Protein Adsorption On Solid Surfaces: Conformational Effectsmentioning
confidence: 99%
“…Enzymes such as Candida rugosa lipase (CRL) and Pseudomonas cepacia lipase (PCL) have been adsorbed on nanostructured polystyrene (PS) and polymethylmethacrylate (PMMA) by simple addition of the lipase solution to the polymeric nanoparticles under protein-friendly conditions (pH 7.6). Adsorption leads to improved performance in terms of activity and selectivity with respect to that shown by lipases adsorbed on the same nonnanostructured carriers, as well as increased enantioselectivity and pH and thermal stability [106]. Karajanagi et al have also examined the structure and function of two enzymes, R-chymotrypsin (CT) and soybean peroxidase (SBP), adsorbed onto single-walled carbon nanotubes (SWNTs).…”
Section: Protein Adsorption On Solid Surfaces: Conformational Effectsmentioning
confidence: 99%
See 1 more Smart Citation